Mathematical model to predict split tensile strength of concretes in crude oil contaminated environments - Ezihe, J. C.; Ugwu, O. O.; Okafor, F. O. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Few concrete components used for constructions within the Niger Delta region of Nigeria are contaminated with crude oil to varying ranges. An investigation into the split tensile behaviour of concretes to crude oil when cured in 10% crude oil/water medium is carried out in this work. In this work, crude oil was used as a fifth ingredient of concrete mix which replaced 5% to 20% of the w/c. The four other components were cement, sand, granite, and water. A designed mix ratio of 1:2:4 with w/c of 0.5 was utilized as the initial component mix design. Scheffe’s simplex theory was used for the five mix ratios in a {5,2} experimental design. This gave rise to ten additional mix ratios and fifteen other additional mix ratios were generated for control purposes. These thirty concrete mix ratios were subjected to laboratory experiments to determine the 7 and 28 days split tensile strengths. The results of the first fifteen split tensile strengths were used for the calibration of the model constant coefficients, while the results from the second fifteen were used as control. A mathematical regression model was derived from the results, with which the split tensile strengths were developed. The derived model was subjected to a two-tailed t-test with 5% significance, which ascertained the model to be adequate with an R2 value of 0.9616 and 0.9227. The study revealed that crude oil presence in a concrete mix can be harmful as it reduces the split tensile strength of concretes.